Assessing the effectiveness of structural and non-structural flood mitigation measures of Bushrod island’s unplanned settlements - Kamara, Abu Sumaila (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2023.